Kaempferol Ameliorates the Inhibitory Activity of Dexamethasone in the Osteogenesis of MC3T3-E1 Cells by JNK and p38-MAPK Pathways - Xie, Baocheng; Zeng, Zhanwei; Liao, Shiyi; Zhou, Chenhui; Wu, Longhuo; Xu, Daohua (Frontiers in Pharmacology, 2021)
Kaempferol has been reported to exhibit beneficial effect on the osteogenic differentiation in mesenchymal stem cells (MSC) and osteoblasts. In our previous study, dexamethasone (DEX) demonstrated inhibitory effect on MC3T3-E1 cells differentiation. In this study, we mainly explored the protective effect of kaempferol on the inhibitory activity of DEX in the osteogenesis of MC3T3-E1 cells. We found that kaempferol ameliorated the proliferation inhibition, cell cycle arrest, and cell apoptosis and increased the activity of alkaline phosphatase (ALP) and the mineralization in DEX-treated MC3T3-E1 cells. Kaempferol also significantly enhanced the expression of osterix (Osx) and runt-related transcription factor 2 (Runx2) in MC3T3-E1 cells treated with DEX. In addition, kaempferol attenuated DEX-induced reduction of cyclin D1 and Bcl-2 expression and elevation of p53 and Bax expression. Kaempferol also activated JNK and p38-MAPK pathways in DEX-treated MC3T3-E1 cells. Furthermore, kaempferol improved bone mineralization in DEX-induced bone damage in a zebrafish larvae model. These data suggested that kaempferol ameliorated the inhibitory activity of DEX in the osteogenesis of MC3T3-E1 cells by activating JNK and p38-MAPK signaling pathways. Kaempferol exhibited great potentials in developing new drugs for treating glucocorticoid-induced osteoporosis.